2014
DOI: 10.1055/s-0033-1353193
|View full text |Cite
|
Sign up to set email alerts
|

Strukturen und Prozesse in der ambulanten Neurorehabilitation

Abstract: In the meantime outpatient centres of neurorehabilitation are well-established as care providers and commonly accepted by service providers. However a comprehensive availability does not exist. The results show comparable structures of the centres, what is mostly determined by the service provider audited regulatory framework. Different concepts result in different processes. There are a lot of hints with respect to different concepts in form and content to implement the legally obligated mandate. In general t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Overall, the conditions of neurorehabilitation in Germany and Austria are not very comparable. The results of our sample of 4 outpatient neurological rehabilitation centres run by one carrier in the Austrian province of Vorarlberg presented here show that, despite the divergent rehabilitation contexts, the instruments employed in the course of a large multicentre study that included 17 German outpatient rehabilitation facilities [6,[13][14][15][16][17] can be meaningfully used for outcome evaluation in the Austrian context. During data collection and analysis, there was no evidence for a limited applicability of the instruments in the Austrian context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the conditions of neurorehabilitation in Germany and Austria are not very comparable. The results of our sample of 4 outpatient neurological rehabilitation centres run by one carrier in the Austrian province of Vorarlberg presented here show that, despite the divergent rehabilitation contexts, the instruments employed in the course of a large multicentre study that included 17 German outpatient rehabilitation facilities [6,[13][14][15][16][17] can be meaningfully used for outcome evaluation in the Austrian context. During data collection and analysis, there was no evidence for a limited applicability of the instruments in the Austrian context.…”
Section: Discussionmentioning
confidence: 99%
“…During data collection and analysis, there was no evidence for a limited applicability of the instruments in the Austrian context. Comparison of the reported sociodemographic and socio-medical indicators of the study participants and the key figures of the similarly designed and carried out multicentric study in Germany [6,[13][14][15][16][17] show similarities and differences between the study populations. In all of our own and comparable studies, there was a high scatter in participation impairments; this can also be observed in a healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Der Anteil der Rehabilitanden, die zu Rehabeginn entgegen der Einschlusskriterien eher der Phase C zuzuordnen sind, liegt mit einem Drittel sicher deutlich höher als in der ambulanten Neurorehabilitation in Deutschland. Im Vergleich dazu gaben in einer Untersuchung der Strukturen und Prozesse in der ambulanten Neurorehabilitation in Deutschland [15] lediglich 18 % der befragten Einrichtungen an, zu einem geringen Anteil regelhaft Rehabilitanden der Phase C bei sich zu behandeln und in der bereits erwähnten multizentrischen Untersuchung lag der Anteil an Rehabilitanden der Phase C, ermittelt über den SINGER-Summenscore, zu Rehabeginn bei 5 % (unveröffentlichtes Ergebnis) [6]. Daher ergeben sich Hinweise auf deutliche Unterschiede in den Rahmenbedingungen ambulanter Neurorehabilitation in Deutschland und Österreich bzw.…”
Section: Auswertungunclassified